Semantic study of the meaning of the expression authentic happiness behind the practice of personal accounting - Rafles Ginting; Eryska Apriwulandari; Lestari Lestari; Tengku Hafiza; Sari Rusmita (AKUNTABEL, 2023)
The practice of personal accounting is a tool for self-screening of students' consumptive attitudes. Budgeting and financial management, which were previously difficult to do, has become more effective because less time is spent on simple day-to-day recording. Recording and budgeting facilitate financial decisions and facilitate long-term financial planning. This was obtained from student feedback as many as 5 (five) informants through face-to-face interviews and direct observation from the results of student daily recordings for a month. From the results of this study, 16 (sixteen) questions were obtained about recording and managing finances. Daily financial records are very useful for personal financial arrangements and financial decisions and play a major role in financial planning. Daily financial records are essential for managing daily personal expenses. That is, as self-control, to curb desires and prioritize needs, as well as being able to make us more realistic and situational.